Analisis Optimalisasi Kinerja Pembekuan Ikan Pada PT. Duta Asia Fasifik Abadi - Surya Sirait, Mentari Kinanti; Bi Rahmani, Nur Ahmadi (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This research was conducted with research objectives, among others, namely to examine the effect of compensation and work experience on the performance of employees of PT. Duta Asia Fasfik Abadi and to examine the effect of compensation on employee performance at PT. Duta Asia Fasfik Abadi and to examine the effect of work experience on employee performance at PT. Duta Asia Fasfik Abadi. The analytical method that I use in analyzing the data is qualitative where this method is used by using activity data that already exists in the field for the sake of drawing conclusions about the company data of PT. ABADI ASIA FASIFIK ABADI, namely by comparing the existing literature references with reality. Which is where the frozen fish service at the company PT. Duta Asia Pacific Abadi is more dominant in fish products because marine products are dominant in fish products as for various types of frozen fish ranging from Ogak, Terisi, Bloat Fish, Sembak, Cincaru, and many more. Not only fish, this fish company also accepts squid freezing service although not too much compared to fish. The results showed that the processing of freezing fish has several stages that must be carried out specifically by each employee, including receiving raw materials, weighing, washing 1, holding, washing 2, preparation in long pan, freezing, storage. While the weakness is in the management of the packaging design, it is still not attractive, there is no special label for PT. Asia Pacific Ambassador Eternal. The fish freezing service at the fish company is Rp. 600-, per pack.